Analyzing Bengkalis e-Government Website Using GTMetrix - Pasaribu, Daniel (eScience Humanity Journal, 2024)
Website is an important information and communication media for disseminating information openly and widely throughout the world. In the world of government, websites are very important as a supporting facility for information and communication needs. The purpose of this research is to analyze the performance of the Bengkalis government website, SiPendekar, using evaluation method. The assessment is conducted using the GTmetrix measurement tool, which gauges website performance using various performance metrics. Based on the assessment result, SiPendekar website performance gain 65% or in grade C which means SiPendekar website performance is relatively good. If the website performance is good, it will automatically influence the interest of people in using the website.